2018
DOI: 10.1016/j.cveq.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Equine Dysautonomia

Abstract: Equine dysautonomia (ED; also known as equine grass sickness) is a neurological disease of unknown cause, which primarily affects grazing adult horses. The clinical signs reflect degeneration of specific neuronal populations, predominantly within the autonomic and enteric nervous systems, with disease severity and prognosis determined by the extent of neuronal loss. This review is primarily focused on the major clinical decision-making processes in relation to ED, namely, (1) clinical diagnosis, (2) selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Three different syndromes can be recognized on the basis of the clinical signs, that are severe in the acute form, moderate in the subacute form, and mild in the chronic form [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three different syndromes can be recognized on the basis of the clinical signs, that are severe in the acute form, moderate in the subacute form, and mild in the chronic form [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Equine dysautonomia (also known as equine grass sickness, EGS) is a life-threatening disease of unknown aetiology, affecting horses. Approximately 80% of the affected animals die within days after the recognition of the first clinical signs; the mortality is reported as 100% in the acute and subacute forms and 50% in the chronic form (McGorum and Pirie, 2018). This polyneuropathy affects both the central and the peripheral nervous system and leads to severe clinical signs, due to gross and microscopic pathological alterations in the ganglions and neurocytes localised primarily in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…This polyneuropathy affects both the central and the peripheral nervous system and leads to severe clinical signs, due to gross and microscopic pathological alterations in the ganglions and neurocytes localised primarily in the gastrointestinal tract. Since its first recognition in 1909 (Tocher et al, 1923), multiple cases have been reported around the world (McGorum and Pirie, 2018;Piccinelli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical signs and severity of the disease are largely defined by degeneration of neurons in the enteric nervous system. The disease almost exclusively appears in grazing horses and, although many agents are being discussed, the causative factor remains to be found [2]. Furthermore, intestinal volvulus and strangulation create ischemia of affected intestine and once necessary perfusion is surgically re-established, intestinal damage is often exacerbated.…”
Section: Introductionmentioning
confidence: 99%